Berguru pada Jogja demokrasi dan kearifan kultural H.M. Nasruddin Anshory Ch, Zainal Arifin Thoha ; editor, H. Soemadi M. Wonohito, H. Marzuki Usman - ANSHORY CH. H.M. Nasruddin; Thoha, Zainal Arifin; Wonohito, H. Sumadi M; Usman, H. Marzuki (2005)
xliii, 278 hlm 21 cm